Effect of lysine level and supplemental soybean oil fed during lactation on sow and litter performance through two parities - Weeden, T.L.; Thaler, R.C.; Li, D.F.; Fitzner, G.L.; Nelssen, Jim L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 158 gilts were fed ad libitum one of the following four diets during lactation: .65% lysine, .75% lysine, .65% lysine + 3% soybean oil, and .75% lysine + 3% soybean oil. These same sows were carried through a second parity on the same lactation diet treatments. In parity 1, lysine level had no effect on feed intake or interval from weaning to estrus. Addition of 3% soybean oil increased the weaning to estrus interval and decreased feed intake, although caloric intake was not different. In parity 2, there was no effect on feed intake from 3% supplemental soybean oil; however, the weaning to estrus interval was still delayed by 2.5 d. Overall, there were no interaction effects from increasing the lysine level and adding 3% soybean oil. Increasing lysine to .75% and adding 3% soybean oil had no effect on sow weight loss, sow backfat loss, pig survivability, litter size at weaning, litter weight at weaning, or average pig weight at weaning. Based on the results of this experiment, it appears that a .65% lysine diet without supplemental fat is adequate during lactation.
Keywords: Swine; Sow; Lactation; Lysine; Soybean oil